Cabrol-Type Aortocoronary Anastomosis Technique in Coronary Artery Bypass Surgery - Kim, Tae Sik; Na, Chan-Young; An, Hyonggin (The Thoracic and Cardiovascular Surgeon, 2016)
Background In conventional coronary artery bypass grafting (CABG), multiple anastomoses in the ascending aorta are needed for multiple coronary targeting. We have introduced a single-site proximal anastomosis technique for multiple coronary targeting. A single anastomosis between the ascending aorta and graft was performed using a side-to-side maneuver (Cabrol type). Additionally, the graft was connected to another graft by end-to-end anastomosis for the coronary artery on the opposite side. We evaluated the long-term clinical outcome and graft patency of this Cabrol-type aortocoronary anastomosis technique.Methods From 2002 to 2012, a total of 483 patients (mean age, 64.6 years) underwent CABG using our Cabrol-type aortocoronary anastomosis technique. The average number of target coronary arteries per person was 3.4 ± 0.6. The mean follow-up duration was 74.2 ± 31.3 months; 98.7% of hospital survivors completed the follow-up. Postoperative coronary computed tomography angiography was performed in 377 patients (81.8%).Results Operative mortality was 4.6%. The actuarial overall survival rates at 1, 5, and 10 years were 97.8 ± 0.7%, 89.3 ± 1.5%, and 69.0 ± 3.9%, respectively. The actuarial major adverse cardiac and cerebrovascular event-free survival rates at 1, 5, and 10 years were 95.7 ± 0.9%, 80.1 ± 2.0%, and 60.8 ± 3.7%, respectively. One- and 5-year patency rates of the Cabrol-type aortocoronary graft were 81.1 ± 2.2% and 61.3 ± 3.6%, respectively.Conclusion Our Cabrol-type aortocoronary anastomosis technique did not have superior clinical outcomes and graft patency compared with conventional CABG. However, this technique might be an alternative option in select patients with atherosclerotic disease of the ascending aorta, or other embarrassing situations.
Keywords: coronary artery disease; coronary artery bypass grafting; graft patency; graft occlusion; Cabrol technique